Note: you did not correctly enter the right expression. After a little research, I am able to find the correct expression which is as follows:
4y+9/7 when y = 8
Therefore, I am solving your query based on evaluating the expression
4y+9/7 when y = 8
Answer:
we conclude that after substituting, the first step is to 'Multiply 8 by 4'.
Explanation:
Given the expression
4y+9/7
As we have to evaluate the given expression for the y=8
substituting y=8 in the expression
4y+9/7
= 4(8)+9/7
According to PEMDAS rule, we first need to do multiplication
Thus, the first step must have to be multiplying 4 and 8.
= 32 + 9/7
= 233/7
Therefore, we conclude that after substituting, the first step is to 'Multiply 8 by 4'.